THE POETICS OF THE UNSPEAKABLE AND «LE FILMIQUE» IN THE WORKS OF ROLANDBARTHES - Ousmanova, Almira (Ukrainian Cultural Studies, 2023)
In the given article the author examines conceptual contribution of Roland Barthes to Film Theory from the standpoint of current debates on the methodology of analysis of the photographic and cinematic images. Barthes’ input to the studies of visuality is being discussed in three interconnected aspects. Firstly, the evolution of Barthes’ analytic approach is traced in the context of the formation of Film Semiotics in France and elsewhere (from the 1960s till now). Secondly, the model of textual analysis, elaborated by Barthes in the late 1960s, is considered in relation to the development of film analysis as a particular mode of reading film as a text. Thirdly, highly nuanced and inventive vocabulary, which Roland Barthes applied to the analysis of film language, seems to be particularly suitable for the phenomenalisation of the insignificant in a cinematic text, that is for the interpretation of the uncoded, open, evanescent, elusive, ineffable meanings in a film. Having elaborated such concepts as "third meaning", textual analysis, punctum, "le filmique", ‘traumatic units of cinema" and others, Roland Barthes provided a conceptual toolkit that allows for the analysis of that what I address here as "the poetics of the unspeakable". This concept, on the one hand, articulates the affective power of cinema as a means of communication, and on the other, characterises the specificity of a cinematic language if compared to other sign systems. Barthes developed the foundations of textual analysis of cinema. He was searching for answers to questions that cannot be solved within the framework of linguistics and semiotics of the text – about the insignificant, non-structural, non-semiotic – and found them in the filmic. His approach to cinema, and later to photography, maintains as a constant the attempt to understand how the viewer can overcome the power of the image: through the analysis of his affect and desire, as well as the identification of the signifiers of the ideology mechanisms. The analysis of the poetics of the unspeakable constitutes the "traumatic" core of film theory – it could be an optics to interpret Barthes’ texts on cinema written between 1960 and 1980.